Yield of Mungbean as Influenced by Planting Geometry and Integrated Fertilizer Management (Bangladesh Agronomy Journal, 2023)
Mungbean production is decreasing because of inappropriate management of fertilizer and plant population so a study was initiated to find out the effect of different combinations of organic and inorganic fertilizers with different plant geometry on the yield of mungbean var. BARI Mung-5. The experiment was laid out in a split- plot design with three replications. The experiment comprised of three level of plant geometry viz. S1= 20 cm × 10 cm, S2= 30 cm × 10 cm and S3= 45 cm × 15 cm, and six level of fertilizers: F0= Control (without fertilizer), F1= Recommended dose of NPK, F2=5 t ha-1 cowdung, F3=5 t ha-1cowdung with recommended dose of NPK, F4= 2.5 t ha-1 cowdung with recommended dose of NPK and F5=2.5 t ha-1 cowdung with half recommended dose of NPK. Among the three spacing, 30 cm × 10 cm (S2) produced maximum seed yield (1022.8 kg ha-1) while the lowest in S3 (834.4 kg ha-1). Cowdung had a significant effect on the seed yield and yield attributes of mungbean. The maximum seed yield (1038.9 kg ha-1) was obtained F4 while minimum (930.0 kg h-1) by applying cowdung @5 t ha-1. Among the treatment combinations, S2F4 was showed maximum yield (1156.7 kg ha-1) when considering stover yield and biological yield. Plant spacing of 30 cm × 10 cm along with 2.5 t ha-1 with recommended dose of 40, 80, 30 kg ha-1 of Urea, TSP, MoP could be more beneficial for the farmers to get maximum yield from var. BARI Mung-5.Bangladesh Agron. J. 2022, 25(2): 97-107